ВСЕМИРНЫЙ ДОКЛАД О НАРКОТИКАХ 2014 год - United Nations Office on Drugs; Crime (United Nations, 2014)
The World Drug Report provides an annual overview of the major developments in drug markets for the various drug categories, ranging from production to trafficking, including development of new routes and modalities, as well as consumption. Chapter 1 of the World Drug Report 2014 provides a global overview of the latest developments with respect to opiates, cocaine, cannabis and amphetamines (including “ecstasy”) and the health impact of drug use. Chapter 2 zeroes in on the control of precursor chemicals used in the manufacture of illicit drugs.